Environmentally friendly disinfection method of coccidia oocysts in the environment - U. M. Saipullaev; M. S. Saipullaev (Юг России: экология, развитие, 2023)
Aim. To test the effectiveness and environmental friendliness of a new method of biothermal treatment of bird litter and disinfectant – Penoks‐2 – in relation to bird coccidia oocysts.Material and Methods. A test of biothermal disinfection of bedding manure and disinfestation of premises for rearing young laying hens (6000 birds), was carried out in the Mugutdinova farm of the Buynaksky district of the Republic of Dagestan. The detection of coccidia oocysts was carried out according to the method of Void and Darling, Methods for the Laboratory Diagnosis of Avian Coccidiosis". The quality of the disinfestation using Penox‐2 solutions was controlled by examining swabs and scrapings taken from the experimental and control surfaces of the premises in accordance with the Rules for Disinfection and Disinfestation of Objects of State Veterinary Supervision. The study of biothermal processes in the litter manure was carried out every 5 days with temperature measurement of piles, while taking samples of the litter for detecting the presence of coccidia oocysts.Results. The studies conducted established that the most environmentally safe method of disinfecting premises is biothermal where the population of replacement laying hens is kept. The temperature in piles 1.5 and 2.0 m high and 2–2.5 m wide reached 65–75°C on the 20–25th day, which ensures the destruction of coccidia oocysts. Production tests have shown that solutions of the new Penox‐2 agent destroy coccidia oocysts in the external environment after irrigation of room surfaces with a content of 3.0% chloramine B through a single application at the rate of 0.5 l/m2 and 3 hours exposure.Conclusion. Tests of a new method of biothermal treatment of litter manure and disinfestation with solutions of Penox‐2 showed high efficiency and environmental safety in the destruction of coccidia oocysts.